Gut-brain communication in Drosophila melanogaster. - Yapici, N. (Current Opinion in Neurobiology, 2025)
Over the past decades, significant advancements have transformed our understanding of the gut-brain circuits in Drosophila melanogaster. In this review, we explore how mapping these circuits and signaling pathways has deepened our knowledge of the neural and hormonal pathways that regulate nutrient preference, feeding behavior, metabolism, and other homeostatic behaviors in flies. We summarize the recent breakthroughs in gut-brain communication and highlight how these advancements have provided valuable insights into the complex relationship between the gut and the brain. Finally, we emphasize the importance of Drosophila as a model system for investigating gut-brain communication. Insights from fly research not only enhance our understanding of fundamental gut-brain biology but also provide promising avenues for identifying molecular targets for therapeutic strategies in humans for gastrointestinal and metabolic disorders.